Constructing and multilateralizing the regional comprehensive economic partnership: An Asian perspective - Shujiro Urata (Asian Development Bank Institute (ADBI), 2013)
In May 2013 the ASEAN+6 countries began to negotiate the Regional Comprehensive Economic Partnership (RCEP). The objective of this paper is to analyze the feasibility of constructing such a region-wide agreement and to examine ways to multilateralize it. The paper first reviews free trade agreement (FTA) developments, and discusses the characteristics and motives of FTAs in East Asia. It then analyzes the contents of major plurilateral FTAs in East Asia, that is ASEAN's five FTAs each with the People's Republic of China, Japan, the Republic of Korea, India, and Australia/New Zealand, which are considered as a base for a region-wide FTA. Finally, the paper examines the feasibility of the RCEP by consolidating the ASEAN+1 FTAs and discusses the possible ways to multilateralize the RCEP.
Keywords: F13; F15; O19; O24; 330; regional integration; economic cooperation; trade; investment; asia